Comparison of the Executive Functions and Mental Toughness of Elite Women's Basketball Players with the Statistical Parameters of the InStat Scout System - Kata Németh; József Márton Pucsok; László Rátgéber; László Balogh, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
In addition to physical skills and fundamental coordination, success in ball sports is significantly influenced by athletes' ability to process information within complex and rapidly changing environments. Executive functions are pivotal for enhancing sports performance. This study elucidates that superior mental toughness, and executive functions contribute to improved sports outcomes. The research assessed the mental toughness of elite Hungarian women's basketball players in the first division using the Sports Mental Toughness Questionnaire (SMTQ) and evaluated their executive functions with the Vienna Test System (VTS) Determination Test (DT). Twenty professional players, with an average age of 24 years (range: 19-35 years), were randomly selected for the study. The sample comprised 14 field players and six center players, with 16 Hungarian and four foreign players. These athletes compete at an elite level in Hungary’s first division and engage in an average of nine weekly training sessions (range: 8-10). The SMTQ and DT tests were administered before daily training sessions between August and September 2022. Data were analyzed using the JASP statistical program, and correlation calculations were performed with the Scipy v1.7.1 module under Python v3.9.7. The results were compared with international statistical data from the InStat Scout system. The findings indicate that the SMTQ and executive functions (DT) of the participating team members were above average. Specifically, field players demonstrated a higher number of correct responses in decision-making situations compared to center players. The athletes’ strength was evidenced by their high SMTQ scores and superior performance on various DT aspects, including executive functions, reactive stress tolerance, and missed reactions. Players with higher SMTQ and DT scores were more likely to excel in the InStat Scout system. Incorporating SMTQ and VTS methods into psychological training for ball-sport athletes could be beneficial. Further research across different populations and team sports is recommended to integrate these findings into athletes' mental preparation strategies.